Moving from Symmetric to Asymmetric Nexus between Oil Price, Exchange Rate and Government Spending in Developing Economy with Focus on Economic Sustainability - Babatunde, David; Victor Bekun, Festus Vıctor; Börü, Mustafa Kerem; Huseynova, Rena (Econjournals, 2025)
Over the past few decades, many developing countries, especially Nigeria, have continuously grappled with sustaining their economies financially despite huge proceeds from the exportation of crude oil and other mineral resources. Leading to under-performance and inefficiencies in these economies. This forms the backdrop for this study, which investigates the link between the oil price, exchange rate, and government spending in Nigeria. To achieve this, the research analysed annual frequency data between 1981 and 2022 using auto-regressive distributed lag (ARDL) and Non-Linear Auto-regressive distributed lag (NARDL) models after checking for unit-root properties. Findings show that oil price (both in linear and non-linear investigations) correlated positively but cannot explain government spending. The exchange rate has a direct and significant linear and non-linear influence on government spending. Given these findings, policies on government spending should be channeled towards sustainable economic diversification to prevent future shocks in the exchange rate and oil price. © 2025, Econjournals. All rights reserved.
Keywords: Dynamic Multiplier; Oil Price; Resource Curse; SDG-8; Shock Evolution; Sustainable Economic Growth